Leptin-Induced Angiogenesis of EA.Hy926 Endothelial Cells via the Akt and Wnt Signaling Pathways In Vitro and In Vivo - Yu, Fei; Fu, Runqing; Liu, Lu; Wang, Xiaoting; Wu, Tingting; Shen, Wei; Gui, Zhipeng; Mo, Xiumei; Fang, Bing; Xia, Lunguo (Frontiers in Pharmacology, 2019)
Angiogenesis involves the activation of endothelial cells followed by capillary formation. Leptin, the protein product of the ob gene, can induce the angiogenic potential of endothelial cells. However, the underlying cellular mechanism still remains to be elicited. We firstly evaluated the in vitro effects of leptin on proliferation and angiogenic differentiation of endothelial cell line EA.hy926. Leptin was found to potently induced cell proliferation, expression of angiogenic gene, migration and tube formation. Then we investigated the roles of the Akt and Wnt signaling pathways in the aforementioned processes. It showed that Akt and Wnt signaling pathways could be activated by leptin, while inhibition of the Akt and Wnt signaling pathways by siRNAs effectively blocked the leptin-induced angiogenesis. Finally, we used electrospinning to fabricated leptin-immobilized linear poly(L-lactide-co-caprolactone) (PLCL-leptin). The in vivo vessel formation of PLCL-leptin was evaluated using subcutaneous implants in Sprague-Dawley rats. The histological and immunofluorescence revealed that cell infiltration with PLCL-leptin was much more significant than that with the control PLCL group. More importantly, the number of laminin+ vessels and CD31+ cells in PLCL-leptin grafts was significantly higher than in control grafts. The study demonstrated that it is via Akt and Wnt signaling pathways that leptin promotes the proliferation and angiogenic differentiation of endothelial cells and the capacity of endogenous tissue regeneration makes the novel leptin-conjugated PLCL promising materials for grafts.